The Warsaw-Berlin ice-marginal spillway near Łęczyca; geology, landforms and their evolution - Forysiak, Jacek; Majecka, Aleksandra; Marks, Leszek; Bujak, Łukasz (Acta Geographica Lodziensia, 2024)
The problem of the functioning of the Warsaw-Berlin ice-marginal spillway presented in the article results from the morphological features of the area and its watershed position. The analysis of the geological structure and identification of the lithology of the sediments filling the buried valley of the bottom of the ice-marginal spillway near Łęczyca were aimed at demonstrating their deposition during the Vistula Glaciation and connections with the activity of proglacial waters and the conditions prevailing in the foreland of the ice sheet. The filling of this fossil form consists of the Vistulian mineral series, which is sandy-muddy, and covered by organic-mineral deposits of the Late Vistulian and Holocene.